How supply chain strategies moderate the relationship between innovation capabilities and business performance. Issue 5 (December 2020) - Zimmermann, Ricardo; Ferreira, Luís Miguel D.F.; Moreira, António Carrizo
Abstract: The purpose of this paper is to study how the fit between innovation capabilities and supply chain (SC) strategies affects business performance. An empirical study based on a sample of 329 companies from Portugal and Brazil was performed to test a theoretical model based on the resource-based view. Linear and hierarchical regression analyses are conducted to test the hypotheses. The different combinations of core and supplementary innovation capabilities and lean and agile SC strategies are empirically tested and discussed. Data reveal that core and supplementary innovation capabilities positively impact on business performance and that SC strategies moderate the relationship between innovation capabilities and business performance. The analysis also shows that the combination of an agile SC strategy and supplementary innovation capabilities offers the greatest opportunities to improve business performance. The results of this study could help managers to choose the most appropriate SC strategy, thus contributing to increasing the impact of innovation capabilities on business performance. This study contributes to the knowledge concerning the consequences of adopting different innovation capabilities and SC strategies on business performance. Highlights: Study how the fit between innovation capabilities (IC) and supply chain (SC) strategies affects business performance. Different combinations of core and supplementary ICs and lean and agile SC strategies are empirically tested and discussed. Core and supplementary ICs positively impact on business performance. The combination of an agile SC strategy and supplementary IC offers the greatest opportunities to improve performance.